Pengaruh Karakter Individu, Sikap Mandiri, Dan Pengetahuan Kewirausahaan Terhadap Minat Berwirausaha (Studi Kasus pada Siswa SMK Yadika 5 di Tangerang Selatan - Widi Wahyudi; Bella Safitri (Universitas 45 Surabaya, 2023)
This study aims to determine the significant effect of Individual Character, Independent Attitude, and Entrepreneurship Knowledge on Entrepreneurial Interest at SMK Yadika 5 in South Tangerang. The population in this study were students of SMK Yadika 5 in South Tangerang. Determination of the sample used in this study as many as 75 respondents using the Slovin formula approach technique. This retrieval uses a probability sampling technique. sampling using the analytical tool used is descriptive (primary data) by using a questionnaire spread yes using a Likert scale. The research analysis tool uses SPSS version 20 software. The results of multiple linear analysis using multiple linear regression analysis method Y = 14,542 + 0,597 (X1) - 0,228 (X2) + 0,401 (X3) + €. The conclusion in this study is that individual character, entrepreneurial knowledge has a significant effect on interest in entrepreneurship. Independent attitude has no significant effect on interest in entrepreneurship.